The essence of social entrepreneurship through a Georgian lens: Social entrepreneurs' perspectives - Iza Gigauri; Mirela Panait; Simona Andreea Apostu; Lukman Raimi (Administrative Sciences, 2022)
The attention to the phenomenon of social entrepreneurship has been especially enhanced during the current turbulent times, as social enterprises have a key role to play in solving social problems caused by the pandemic. Currently, social entrepreneurship is still an undeveloped area in Georgia, but it has the potential to contribute to the country's economy and improve the social, ecological, and economic conditions of society. This paper analyses the concept in Georgia and explores social entrepreneurship from the social entrepreneurs' perspective. A qualitative interview method was applied to collect the data for this study, and semi-structured interviews were conducted with the seventeen Georgian social entrepreneurs from May-June 2021. The research reveals the drivers of social entrepreneurs and investigates the financial sources of social enterprises. It also discusses the practice of social entrepreneurship in terms of preventing and supportive factors while adopting the concept in transition economies, particularly in Georgia. The research demonstrated an urgent need for legislation to regulate the field of social entrepreneurship and formalize it.
Keywords: 350; funding; Georgia; innovation; social enterprise; social entrepreneur; social entrepreneurship; sources